Portlandia. Season three [videorecording (DVD)] - Armisen, Fred, 1966-; Brownstein, Carrie, 1974-; Krisel, Jonathan; Sevigny, Chloë (Distributed by Video Service Corp., 2013)
A hit sketch comedy series that is driven by hilarious character-based shorts, all of which take place in "Portlandia", the creators' dreamy and absurd rendering of Portland, Oregon, where 90s culture reigns supreme and political correctness is all the rage.